Cross-reactive antibody against human coronavirus OC43 spike protein correlates with disease severity in COVID-19 patients: a retrospective study. Issue 1 (1st January 2021) - Guo, Li; Wang, Yeming; Kang, Liang; Hu, Yongfeng; Wang, Linghang; Zhong, Jingchuan; Chen, Hong; Ren, Lili; Gu, Xiaoying; Wang, Geng; Wang, Conghui; Dong, Xiaojing; et al.
ABSTRACT: Seasonal human coronaviruses (HCoVs) including HCoV-229E, -OC43, -NL63, and -HKU1 widely spread in global human populations. However, the relevance of humoral response against seasonal HCoVs to COVID-19 pathogenesis is elusive. In this study, we profiled the temporal changes of IgG antibody against spike proteins (S-IgG) of SARS-CoV-2 and seasonal HCoVs in 838 plasma samples collected from 344 COVID-19 patients. We tested the antigenic cross-reactivities of S protein between SARS-CoV-2 and seasonal HCoVs and evaluated the correlations between the levels of HCoV-OC43 S-IgG and the disease severity in COVID-19 patients. We found that SARS-CoV-2 S-IgG titres mounted until days 22–28, whereas HCoV-OC43 antibody titres increased until days 15–21 and then plateaued until day 46. However, IgG titres against HCoV-NL63, −229E, and -HKU1 showed no significant increase. A two-way cross-reactivity was identified between SARS-CoV-2 and HCoV-OC43. Neutralizing antibodies against SARS-CoV-2 were not detectable in healthy controls who were positive for HCoV-OC43 S-IgG. HCoV-OC43 S-IgG titres were significantly higher in patients with severe disease than those in mild patients at days 1–21 post symptom onset (PSO). Higher levels of HCoV-OC43 S-IgG were also observed in patients requiring mechanical ventilation. At days 1–10 PSO, HCoV-OC43 S-IgG titres correlated to disease severity in the age group over 60. Our data indicate that there is a correlation between cross-reactive antibody against HCoV-OC43 spike protein and disease severity in COVID-19 patients.